2018
DOI: 10.1080/17425247.2018.1424825
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor microenvironment to curb chemoresistance via novel drug delivery strategies

Abstract: Tumor is a heterogeneous mass of malignant cells co-existing with non-malignant cells. This co-existence evolves from the initial developmental stages of the tumor and is one of the hallmarks of cancer providing a protumorigenic niche known as tumor microenvironment (TME). Proliferation, invasiveness, metastatic potential and maintenance of stemness through cross-talk between tumors and its stroma forms the basis of TME. Areas covered: The article highlights the developmental phases of a tumor from dysplasia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 287 publications
0
6
0
Order By: Relevance
“…[20][21][22]49 These off-target effects or consequences for cell-cell interactions are equally important, as they are involved in CAM-DR. 10,11 The 3D BM-myeloma model can be used to study therapies targeting these interactions, as shown by selectively targeting myeloma cells using VLA-4 targeted liposomes, to overcome CAM-DR. Also other novel therapies or drug delivery strategies targeting the tumor microenvironment can potentially be tested within the 3D BM-myeloma model, such as gamma secretase inhibitors, or the co-delivery of cytotoxic agents. [50][51][52] In contrast to 2D culture systems, the 3D BM-myeloma model provides the possibility to test therapies on patientderived myeloma cells. Currently available treatment options for myeloma have improved patient outcomes, 4 but do not achieve optimal treatment responses for a substantial proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22]49 These off-target effects or consequences for cell-cell interactions are equally important, as they are involved in CAM-DR. 10,11 The 3D BM-myeloma model can be used to study therapies targeting these interactions, as shown by selectively targeting myeloma cells using VLA-4 targeted liposomes, to overcome CAM-DR. Also other novel therapies or drug delivery strategies targeting the tumor microenvironment can potentially be tested within the 3D BM-myeloma model, such as gamma secretase inhibitors, or the co-delivery of cytotoxic agents. [50][51][52] In contrast to 2D culture systems, the 3D BM-myeloma model provides the possibility to test therapies on patientderived myeloma cells. Currently available treatment options for myeloma have improved patient outcomes, 4 but do not achieve optimal treatment responses for a substantial proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery into tumors can be affected by various cellular and histological factors that undermine the efficacy of cancer therapeutic drugs. ( 32,33 )…”
Section: Resultsmentioning
confidence: 99%
“…Drug delivery into tumors can be affected by various cellular and histological factors that undermine the efficacy of cancer therapeutic drugs. (32,33) To address this issue, we sought to investigate the distribution of VP to tumor-bearing livers. VP is a benzoporphyrin derivative that exhibits red fluorescence on excitation at 420-440 nm, allowing the distribution and relative concentration of the drug within tissue to be determined based on fluorescence intensity.…”
Section: Delivery Of Vp Into Hcc Is Impairedmentioning
confidence: 99%
“…Moreover, evidences have demonstrated that the expression level of CDK1 correlated well with immune in ltration [35,36]. In the investigation of immune in ltration, Myeloid-derived suppressor cells (MDSCs) expression was positively correlated with CDK1 expression by using the UALCAN.…”
Section: Discussionmentioning
confidence: 99%